Hubungan Job Distress, Burnout, dan Perilaku Agresif di Tempat Kerja - Junaedi, Christofera Marliana (Kajian Manajemen dan Bisnis, 2010)
Although difficult to measure, job related stress and burnout is important to be studied and researched on as it may cause not only negative outcomes in individuals such as depression, guilt, exhaustion or fatigue, and loss of motivation, but also negative outcomes for organizations such as increasing absenteeism and turnover, and declining productivity.